Earnings and Dividend Announcements: Are They Interactive? Evidence from the French Context - Kouki, Mondher (International Journal of Economics and Financial Issues, 2017)
In this study, we examine abnormal stock returns surrounding contemporaneous earnings and dividend announcements in order to shed more light on the substantive relationship between these two financial signals. Our focus is to investigate the possible complementary or substitutive effect on a sample of French firms. The empirical evidence indicates that information content of dividends should be examined jointly with earnings announcement. The coefficients of all the dummy variables are uniformly negative and significant above the 1% confidence level. These results are inconsistent with those of Kane et al (1984). The significant coefficients support the corroboration hypothesis showing a negative interaction between earnings and dividends. This evidence suggests that investors evaluate the two announcements as two offsetting effects in order to meet any unexpected change in the firm’s financial policy. Keywords: earnings, Dividends, event studies, corroboration effect. JEL Classifications: G14, G20, G31, G35, M48